Assessment of a novel nanoparticle hyperthermia therapy in a murine model of osteosarcoma. Issue 8 (11th October 2018) - Tuohy, Joanne L.; Fogle, Jonathan E.; Meichner, Kristina; Borst, Luke B.; Petty, Christopher S.; Griffith, Emily H.; Osborne, Jason A.; Lascelles, B. Duncan X.
Abstract: Objective: To evaluate the effects of nanoparticle hyperthermia therapy on monocyte function and tumor‐derived factors associated with macrophage polarization in a murine osteosarcoma model. Study design: Experimental study. Animals: Female C3H mice. Methods: Peripheral blood monocyte cell surface phenotype, monocyte chemotaxis, tumor messenger RNA expression, and survival were compared among osteosarcoma (OS)‐bearing mice treated with nanoparticle hyperthermia therapy, OS‐bearing mice with osteomyelitis, OS‐bearing mice, vehicle control mice, and normal control mice. Results: OS‐bearing mice with osteomyelitis had a higher proportion of "nonclassical" monocytes (Ly6C lo ) compared with all other experimental groups. There were alterations in monocyte expression of multiple chemokine receptors among experimental groups including CXCR2, CCR2, and CXCR4. Monocytes from OS‐bearing mice treated with hyperthermia therapy exhibited greater chemotaxis compared with monocytes from OS‐bearing mice with osteomyelitis. Conclusion: OS likely induced alterations in monocyte phenotype and function. Nanoparticle hyperthermia therapy increased in vitro monocyte chemotaxis. Clinical impact: Enhancing monocyte/macrophage function in dogs with OS may enhance antitumor immunity.